EVALUATION OF TOURISM MANAGEMENT IN THE BOSQUE DE PÓMAC HISTORIC SANCTUARY, PERU - Chavez, Jorge Mario; Tetto, Alexandre França; Reynel, Carlos Augusto; Souza, Nilton José (Floresta, 2022)
The objective of this research was to evaluate the management of tourism in the Bosque de Pómac Historic Sanctuary, in the region of Lambayeque, Peru, by developing a methodology using criteria and variables related to the sustainability of the protected natural area and the activity. Although several methodologies can be used to evaluate the general management of natural protected areas, this study focuses exclusively on tourism-related activities in one specific area. To develop the methodology, international documents related to tourism, nature, and culture were reviewed, and six criteria were obtained to evaluate the progress of tourism management in natural protected areas: Management Governance, Heritage Conservation, Identity and Authenticity, Equity and Inclusion, Marketing and Commercialization, and Visitor Experience. Subsequently, fifty-six variables were determined to be evaluated within the six criteria. A numerical evaluation matrix was designed in order to be applied to the criteria and variables with four rating levels; semi-structured interviews were conducted with twenty-five specialists in the area of tourism and natural protected areas (businesspeople, academics, consultants, public officials, as well as local entrepreneurs) linked to the protected area, and information was obtained from technical reports and field inspections. Using the scores, it was determined that the sanctuary has positively developed the criteria of Governance, Conservation, and Visitor Experience, while the issues related to Cultural Identity and Authenticity, as well as Inclusion and Equity, still need to be improved. Keywords: governance, sustainability, protected areas, sustainable tourism.